Providing Legal Assistance to the Rights of the Defendant in the Case of Murder in Self-Defense - Miftakhul Ihwan (Universitas Negeri Semarang, 2021)
Law No. 16 of 2011 concerning legal aid, it is stated that legal aid is legal services provided by legal aid providers free of charge to legal aid recipients. In order to ease the burden of life for groups of people who are economically incapable, and also useful for creating justice and legal protection for the general public, legal aid is formed where the assistance is given to protect the rights of the accused as social beings, especially those included in the incapacitated or poor. Even so, the defendant's actions have clearly violated the law, but the law must also ensure that the rights of the accused are fulfilled as citizens, especially in terms of human rights. Legal aid institutions play an important role in providing legal assistance to people who need legal assistance to guarantee their rights before the law. The problem in this research is how to implement the provision of legal aid to defendants who are economically incapable of murder cases on the basis of self-defense. What are the inhibiting factors for the implementation of providing legal aid to defendants who are economically incapable? The conclusion in this study is that the law clearly stipulates that every citizen has the right to legal guarantees and protection, the state must protect every human right of its citizens well regardless of position status or SARA.